2022
DOI: 10.1021/acsnano.2c05339
|View full text |Cite
|
Sign up to set email alerts
|

Size- and Ligand-Dependent Transport of Nanoparticles in Matricaria chamomilla as Demonstrated by Mass Spectroscopy and X-ray Fluorescence Imaging

Abstract: Matricaria chamomilla flowers were incubated with gold nanoparticles of different sizes ranging from 1.4 to 94 nm. After different incubation times of 6, 12, 24, and 48 h, the gold distribution in the flowers was destructively measured by inductively coupled plasma mass spectrometry (ICP-MS) and non-destructively measured by X-ray fluorescence imaging (XFI) with high lateral resolution. As a control, the biodistribution of iodine ions or iodine-containing organic molecules (iohexol) was determined, in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 77 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…This could be associated with the uptake of NPs within plants because advanced nanotechnologies (i.e., inductively coupled plasma mass spectrometry and X-ray fluorescence imaging) have shown a clear sizedependent transport/uptake of NPs in plants. 56 Overall, the beneficial effects of nano-Fe 3 O 4 on plants were size-and concentration-dependent; the smallest Fe yielded the highest growth promotion. 30 In the present study, the contents of the main root antioxidant enzymes, SOD and POD, with the addition of 0.05% nano-Fe 3 O 4 were higher than those under 0.01% nano-Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This could be associated with the uptake of NPs within plants because advanced nanotechnologies (i.e., inductively coupled plasma mass spectrometry and X-ray fluorescence imaging) have shown a clear sizedependent transport/uptake of NPs in plants. 56 Overall, the beneficial effects of nano-Fe 3 O 4 on plants were size-and concentration-dependent; the smallest Fe yielded the highest growth promotion. 30 In the present study, the contents of the main root antioxidant enzymes, SOD and POD, with the addition of 0.05% nano-Fe 3 O 4 were higher than those under 0.01% nano-Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 94%
“…In the present study, the accumulation of nano-Fe 3 O 4 significantly increased plant antioxidant enzymes, which was in line with Cao et al, who demonstrated that nano-Fe 3 O 4 activated the antioxidative system in plants. This could be associated with the uptake of NPs within plants because advanced nanotechnologies (i.e., inductively coupled plasma mass spectrometry and X-ray fluorescence imaging) have shown a clear size-dependent transport/uptake of NPs in plants . Overall, the beneficial effects of nano-Fe 3 O 4 on plants were size- and concentration-dependent; the smallest Fe yielded the highest growth promotion .…”
Section: Resultsmentioning
confidence: 99%
“…However, while the optical properties of AuNPs are crucial for their function in biosensors, their toxicity, varying with size and shape, cannot be overlooked. 22 Larger NPs are more prone to immune activation, and their shape influences their interactions with immune cells. Spherical and cubic AuNPs, for instance, are less likely to be phagocytosed compared to rod-shaped ones but may induce significant pro-inflammatory cytokine secretion.…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…These NPs' toxicity is contingent on their physical attributes, such as size, shape, and surface properties. 22 Particularly concerning are smaller AgNPs, which can disrupt cellular structures, induce ROS production, and lead to DNA damage, resulting in apoptosis and necrosis. 23,76 NPs enter the bloodstream, their high surface energy leads to the adsorption of plasma proteins, forming a protein corona, 77 which can be problematic, especially if the adsorbed proteins are immunoglobulins or complements.…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…However, it should be noticed that in vivo fluorescence imaging often cannot provide detailed anatomical distribution of nanoparticles within organs, and in certain cases, the limited penetration depth and tissue autofluorescence could potentially lead to misleading assessments of nanoparticle transport dynamics noninvasively. These limitations can be partially overcome by utilizing nanoparticles that emit at the first or second near-infrared (NIR) window. , Other optical imaging techniques such as photoacoustic imaging (PAI) offers high spatial and temporal resolution based on the optical absorption of nanoparticles and subsequent generation of ultrasound signals, which allow researchers to distinguish nanoparticles deeper within tissues compared to traditional optical methods. , On the other hand, X-ray imaging techniques, such as computerized tomography (CT), provide three-dimension (3D) high spatial resolution for visualizing nanoparticles without restriction in penetration depth, but are limited to nanoparticles composed of elements with high atomic number like I, Au, Bi, Pt, and Ta. An ionizing radiation-free alternative approach is to use MRI, which involves attaching paramagnetic contrast agents, such as Gd-chelated contrast agents, to nanoparticles. , MRI allows for real-time monitoring of the transportation of numerous magnetic nanoparticles and noninvasively provides high-resolution images of the interactions between nanoparticles and various organs . Some nanoparticles can be labeled with radioactive elements, such as 124 I, 18 F, 64 Cu, allowing them to be tracked using nuclear imaging techniques, such as SPECT and PET, which are highly sensitive and quantitative. To further understand the interactions of nanoparticles at the cellular or molecular level, electron microscopy and various high-resolution optical microscopy techniques, such as confocal microscopy and multiphoton microscopy are often employed. , For instance, intravital imaging, which enables tacking nanoparticles in live animals at microscopic resolution, becomes a crucial tool to reveal the mechanisms of nanoparticle transport in vivo …”
Section: Tools For Investigating In Vivo Nanoparticle Transportmentioning
confidence: 99%